2009
DOI: 10.1589/jpts.21.141
|View full text |Cite
|
Sign up to set email alerts
|

Differing Responses of Satellite Cell Activity to Exercise Training in Rat Skeletal Muscle

Abstract: Abstract.[Purpose] The present study examined satellite cell and hepatocyte growth factor (HGF) responses to exercise intensity in the rat soleus muscle.[Methods] HGF levels assessed during postnatal growth of the gastrocnemius muscle. Depression of HGF levels occurred up to postnatal week 4, so 4-weekold rats were used the exercise training experiment. Rats walked or ran at speeds of 16 or 24 m/min, at -16% grade, 30 min/trial. Soleus muscles were removed after 72 h. Animals were injected with the thymidine a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 25 publications
2
6
0
Order By: Relevance
“…In the present study, the plantaris muscle wet weight to body weight, and the mRNA expressions of HGF and MyoD , plateaued at 8 weeks of age during postnatal growth. These results are consistent with those of previous studies using HGF enzyme-linked immunosorbent assay and immunohistochemistry 11 , 15 , 16 ) . Therefore, 8-week-old rats in which the effect of growth was small were used in the subsequent study.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In the present study, the plantaris muscle wet weight to body weight, and the mRNA expressions of HGF and MyoD , plateaued at 8 weeks of age during postnatal growth. These results are consistent with those of previous studies using HGF enzyme-linked immunosorbent assay and immunohistochemistry 11 , 15 , 16 ) . Therefore, 8-week-old rats in which the effect of growth was small were used in the subsequent study.…”
Section: Discussionsupporting
confidence: 93%
“…MyoD and myogenin belong to a class of myogenic differentiation factors, which are expressed in myogenic cells during proliferation and differentiation, and in the present study, expression of these genes indicated satellite cell activation 11 , 17 , 18 , 19 ) . The mRNA expressions of MyoD , myogenin , and c-Me t immediately increased after the 5-min electrical stimulation.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…In this study (24 m/min, -16°, 30 min), however, MyoD mRNA expression showed no changes, and myogenin mRNA expression at P24 was about 1.7-fold that in CON, although the difference was not significant. Our previous study showed that BrdU-positive cells were significantly elevated using the same exercise protocol in 4-wk-old rats 18) . The difference between the present and previous studies was apparently due to age, as the number of satellite cells decreased in SOL, and the number of satellite cell activated by exercise is known to decrease with aging 3) .…”
Section: Discussionmentioning
confidence: 86%
“…Rats in the experimental groups performed running at 24 m/min on a treadmill with 16° decline for 30 min. The exercise protocol was based on that used in previous studies 3, [16][17][18] . After the exercise, rats were returned to their cages and given ad libital access to food and water.…”
Section: Methodsmentioning
confidence: 99%